Improvement of alexithymia in patients treated in mental health services for personality disorders: a longitudinal, observational study - Sayar, Hanna; Wilberg, Theresa; Eikenæs, Ingeborg Ulltveit-Moe; Ekberg, Andreas; Leitemo, Kai; Morken, Katharina Teresa Enehaug; Oftedal, Eileen; Omvik, Siri; Ulvestad, Dag Anders; Pedersen, Geir; Kvarstein, Elfrida Hartveit (Frontiers in Psychiatry, 2025)
BackgroundThe majority of mental health services include patients with personality disorder (PD) and comorbid conditions. Alexithymia, a psychological construct referring to difficulties in identifying and describing internal mental states, may represent a challenge to the psychotherapeutic treatment of patients with PD. This study aimed to investigate the prevalence of alexithymia among patients in specialized PD mental health services, differences according to PD severity and PD type, and the longitudinal course of alexithymia during treatment.MethodsThe study included 1,019 patients treated in specialized PD treatment units, with 70% of them with personality difficulties above the PD diagnostic threshold [borderline PD, 31%; avoidant PD, 39%; PD not otherwise specified (PD-NOS), 15%; other PDs, 15%; and more than one PD, 24%]. Alexithymia was measured repeatedly throughout treatment using the Toronto Alexithymia Scale (TAS-20) self-report questionnaire. Supplementary outcomes included global psychosocial function and health-related life quality. Linear mixed models were applied for data analysis.ResultsAlexithymia was highly prevalent in the sample: 53% of subjects reported high levels and 20% moderate levels. The TAS-20 subscale Difficulty Identifying Feelings was more strongly associated with borderline PD, while the subscale Difficulty Describing Feelings was more closely linked to avoidant PD. For all TAS subscales, poorer abilities were associated with more severe PD, higher levels of anxiety and depression, and poorer psychosocial functioning and life quality. Both alexithymia and measures of psychological functioning improved significantly during treatment with moderate effect sizes regardless of initial PD status. In total, 19% of the patients reported full remission of alexithymia.ConclusionAlexithymia is a common problem among patients with PDs and is associated with mental health difficulties and psychosocial dysfunction, with rates varying across PD type and severity. The study demonstrates moderate improvement of alexithymia during treatment in specialized PD mental health services. Further research should evaluate the effectiveness of different treatments and interventions in reducing alexithymia among PD patients.